Social Adaptation, Self-Confidence and their Relation to Student Achievement Motivation of Madrasa Senior High School 1 Bogor Indonesia in Generating Student with Character - Dahlan R, M. (Opción, 2019)
Social adaptation, self-confidence and their relation to Student achievement motivation of Madrasa Senior high School 1 Bogor Indonesia in generating student with character. The study aimed to find out social adaptation, self-confidence and their relationship with achievement motivation in the Madrasa Senior high School 1 Bogor Indonesia in generating students with character. The sample in this study were 10th grade students with a total of 285 students. The results of this study indicate that; Firstly, the social adaptation variable and the achievement motivation variable were positively correlated between as calculated by Pearson Correlation, and the correlation coefficient value between these variables was 0.354. The coefficient of determination in this analysis obtained a value of 0.125, which means that 12.5% of the achieve- ment motivation variables can be explained from the social adaptation varia- ble. Secondly, self-confidence variable and achievement motivation variable were positively related, the magnitude of the relationship between social adaptation variable and achievement motivation variable obtained by the correlation coefficient between these variables that was 0.541. The coeffi- cient of determination in this analysis obtained 0.292 which means that 29.2% of the variables of achievement motivation can be explained by self- confidence variable. Thirdly, between social adaptation variable and -self-confidence related together with achievement motivation variable , so it was obtained the correlation coefficient value of 0.571. The determination coefficient value obtained was 0.326, which means that 32.6% variation in values on variables Achieve- ment motivation (Y) can be explained by social adaptation (X1) and self- confidence from (X2) together. Based on the results of the study it can be said that social adaptation (X1), self-confidence (X2) were related to achievement motivation (Y). In general, it can be said that social adaptation and self-confidence were related to the achievement motivation of Madrasa Senior high School 1 Bogor Indonesia in generating student with character